2013
DOI: 10.1002/etc.2086
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of contaminated sediments by an amphipod (Melita plumulosa), A harpacticoid copepod (Nitocra spinipes), and a snail (Phallomedusa solida)

Abstract: Abstract-The distribution of contaminants is seldom homogeneous in aquatic systems. In the present study, the avoidance response of Melita plumulosa, Nitocra spinipes, and Phallomedusa solida when exposed to contaminated sediments was investigated. Test vessels were designed to allow the congruent placement of two sediments and assessment of the movement of organisms between the sediments. When exposed to reference sediment, each species dispersed evenly between test chambers regardless of differences in sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Furthermore, while there were no mortalities in the control sediment, the only other experimental sediment to show no clam mortality was the most contaminated RC Top sediment. The ability to avoid contaminated sediments has been demonstrated in a number of invertebrates (Ward et al, 2013a). While avoidance behaviour may prevent or postpone acute toxicity, slow avoidance responses to contaminated sediments may still elicit sublethal effects, as shown by Ward et al (2013b).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, while there were no mortalities in the control sediment, the only other experimental sediment to show no clam mortality was the most contaminated RC Top sediment. The ability to avoid contaminated sediments has been demonstrated in a number of invertebrates (Ward et al, 2013a). While avoidance behaviour may prevent or postpone acute toxicity, slow avoidance responses to contaminated sediments may still elicit sublethal effects, as shown by Ward et al (2013b).…”
Section: Discussionmentioning
confidence: 98%
“…Thigmotaxis has been demonstrated in rodents (Treit and Fundytus, 1988;Simon, Dupuis and Costentin, 1994), zebra fish (Richendrfer et al, 2012;Schnörr et al, 2012;Baiamonte et al, 2016) and crayfish (Tierney et al, 2016) as an anxiety-like behaviour used for the assessment of anxiolytic and anxiogenic compounds. In ecotoxicology, behavioural studies have demonstrated differential inter-species sensitivity to contaminants in activity (Gerhardt et al, 2002), response to predators (Gutierrez, Paggi and Gagneten, 2012), aggression (Tierney et al, 2004), and avoidance (Ward, Simpson and Jolley, 2013) behaviours. However, inter-species variability in the baseline unconditioned behaviours of model organisms is currently understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Results of past studies have demonstrated the ability of benthic organisms to avoid contaminated sediment which suggests that exposure to contaminated sediment in the environment may not be continuous. 16,17 Instead, it is more likely that organisms will come into contact with contaminated sediment as short intermittent exposures similar to aquatic pulse exposures. Ward et al 17 demonstrated that the rate of avoidance of contaminated sediments by an amphipod, harpacticoid copepod, and a snail differed significantly.…”
Section: ■ Introductionmentioning
confidence: 99%